Gastos em campanhas políticas e popularidade nas redes sociais: um estudo sobre os resultados das eleições para vereadores no município de São Paulo em 2016 - Reis, Paula Cristina Gonçalves (2018)
The objective of this dissertation is to analyze the different categories of expenditures in electoral campaigns and the impact of social media on the performance of candidates for the position of São Paulo city councilor in the municipal elections of 2016. For this purpose, we use electoral data from the Brazilian Superior Electoral Court and data collected from the Internet. The determinants of the number of votes are estimated by linear and hierarchical regressions. In addition, linear determinants of campaign donations sources are also estimated. The main results indicate that the political capital, the candidate's wealth, and party coalitions have positive and significant effects on the amount of campaign donation. With regard to the determinants of the number of votes, spending on Internet, radio, TV, and print campaigns have positive effects on the number of votes. Moreover, the results show that the use of the social networks Facebook and Twitter produce significant impacts in the elections.